An overdue catalyst: Limitations imposed by COVID‐19 improved capacity building in community‐led environmental education in Madagascar. Issue 5 (24th April 2023) - West, Kathy; Tecot, Stacey; Walker‐Bolton, Amber D.; Borgerson, Cortni; Wright, Patricia C.; Razafindravony, Lovasoa; Andriamiadanarivo, Andry; Andrianoely, Dina; Celestain, Jean; Elison, Pascal; Jordan, Jessie; Liu, Arielle; et al.
Abstract: The COVID‐19 pandemic caused by the SARS‐CoV‐2 virus brought many primatology research programs and conservation efforts to a halt. After Madagascar closed its borders during March 2020, many on‐site international project leaders and researchers returned to their home countries when their programs were delayed or canceled. Madagascar remained closed to travelers until November 2021, when it reopened to international flights. The 20‐month absence of international researchers allowed many local Malagasy program staff, wildlife professionals, and community leaders to step into new leadership roles and responsibilities. Many programs that already had strong Malagasy leadership and meaningful collaborations with local communities flourished, while others either swiftly strengthened these attributes or faced challenges from pandemic‐related travel restrictions. Here, we describe how the coronavirus pandemic events of 2020–2021 initiated long‐overdue shifts in outdated models of internationally led primate research and education projects in communities living alongside primates at risk of extinction. We discuss the benefits and challenges of pandemic‐induced changes within five primatological outreach projects, as well as how we can use these experiences to improve community‐led environmental education and conservation awareness in the future. Abstract : The COVID‐19 pandemic severely impacted primate research, conservation, and outreach but ultimately led to a shifting of leadership roles from foreign to indigenous people, strengthening community‐based capacity and conservation within communities living alongside primates at risk of extinction. Highlights: The pandemic events of 2020–2021 initiated long‐overdue shifts in internationally led research and education project roles, and facilitated enhanced local leadership within communities living alongside primates at risk of extinction. Locally‐based people added to their professional and technical skill‐sets in the field of primate ecology, providing a foundation upon which they could secure conservation‐compatible livelihoods. Technology made international collaborations and project support possible. Access to technology is crucial to growing capacity within Malagasy communities, but is still unreliable or non‐existent in many rural areas of Madagascar.